2007
DOI: 10.2139/ssrn.997147
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Study of Growth Regressions

Abstract: Using Monte Carlo simulations, this paper evaluates the bias properties of common estimators used in growth regressions derived from the Solow model. We explicitly allow for measurement error in the right-hand side variables, as well as country-specific effects that are correlated with the regressors. Our results suggest that using an OLS estimator applied to a single cross-section of variables averaged over time (the between estimator) performs best in terms of the extent of bias on each of the estimated coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 118 publications
(151 citation statements)
references
References 44 publications
4
146
1
Order By: Relevance
“…The growth empirics method directly estimates the transitional growth equations (6) and (7), which allows the explicit estimation of the education share β. Holtz-Eakin (1993), Vohra (1996), Vohra (1997), Garofalo and Yamarik (2002), Mullen and Williams (2005), Yamarik (2006) use the growth empirics approach and estimate an education share β ranging from less than 0.20 (Vohra 1996(Vohra , 1997 to over 0.50 (Mullen and Williams 2005). As predicted by Hauk and Wacziarg (2009), the cross-sectional estimates of β are higher than the panel FE and GMM-D estimates.…”
Section: Previous Estimates Of the Education Share Of Incomementioning
confidence: 99%
See 2 more Smart Citations
“…The growth empirics method directly estimates the transitional growth equations (6) and (7), which allows the explicit estimation of the education share β. Holtz-Eakin (1993), Vohra (1996), Vohra (1997), Garofalo and Yamarik (2002), Mullen and Williams (2005), Yamarik (2006) use the growth empirics approach and estimate an education share β ranging from less than 0.20 (Vohra 1996(Vohra , 1997 to over 0.50 (Mullen and Williams 2005). As predicted by Hauk and Wacziarg (2009), the cross-sectional estimates of β are higher than the panel FE and GMM-D estimates.…”
Section: Previous Estimates Of the Education Share Of Incomementioning
confidence: 99%
“…The validity of the additional first-difference instruments can be tested using a Difference-in-Hansen test comparing the Hansen test results of the first-differenced and system GMM estimators. Hauk and Wacziarg (2009) conduct Monte Carlo simulations on Eq. (9) allowing for measurement error and correlation between the regressors and state-specific effects.…”
Section: Econometric Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the presence of measurement error, mainly in the income distribution variables, fixed effects estimation would exacerbate the measurement-error bias and produce unreliable results. Hauk and Wacziarg (2004) find that cross-sectional (OLS) approaches lead to 6 If there are omitted variables that are simultaneously correlated with (1) past events, (2) the initial values of the explanatory variables, and (3) the regression residual, endogeneity bias may be introduced in a cross-sectional setting such as this one. However, using a long 10-year window minimizes these problems.…”
Section: The Empirical Modelmentioning
confidence: 99%
“…In a Monte Carlo examination of growth empirics with modest measurement error,Hauk and Wacziarg (2004) found that the biases from omitting the fixed effects in a cross-sectional approach tended to offset the measurement error bias, generating relatively accurate estimates. However, in fixed effects models, the measurement error was exacerbated by the fixed effects (within) differencing, which led to results that were multiple fold more biased than cross-sectional approaches, producing results that were often the wrong sign (also seePartridge 2005).9 All variables are listed in AppendixTable 5, which also includes weighted descriptive statistics of all the variables for the entire sample, as well as for MA and non-MA counties.…”
mentioning
confidence: 99%